Problematika Buruh Outsourcing Pasca Putusan Mahkamah Konstitusi Nomor 91/PUU-XVIII/2020 - Siti Zumrah Koly; Saartje Sarah Alfons; Merlien Irene Matitaputty (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Changes to the provisions regarding outsourcing in the Job Creation Law have substantively eliminated legal protection for outsourced workers and workers in general and perpetuated the contract system by expanding the scope of work of outsourced workers.Purposes of the Research: This writing aims to find out the problems experienced by outsourcing workers after the decision of the consitutional court number 91/PUU-XVIII/2020.Methods of the Research: The research method in this paper uses a normative juridical research type, namely the process to find the rule of law, legal principles and legal doctrine to answer the legal issues faced. By using the research approach statue approach (approach of Act), conceptual approach (conceptual approach), philosophical approach and sociological approach as a supporting approach.Results of the Research: Based on the results of the study, it was  found that after decision of the constitutional court number 91/PUU-XVIII/2020 brought several problems for workers, especially outsourcing workers as contained in law number 11 of 2020 concerning job creation and also had not accommodated the perpective of Indonesian legal products regarding that fulfillment of labor rights in law number 11 of 2020 concerning job creation, including : (1) continuing to perpetuate the outsourcing system which was massively rejected when it was encated in law number 13 of 2003 concerning manpower, (2) the loss of restrictions on the types of work that can be outsourced in order to benefit the company to reduce production costs in terms of wages because the outsourcing system in determining wages has three components that are distibuted, namely outsourcing companis, outsourcing workers, and service user companies, (3) threatened with unilateral layoffs because in the changes to the provisions for layoffs in law No or 11 of 2020 concerning job creation states that layoffs are sufficient to be carried out throught notification from.